Proceedings of the 12th Annual Conference of the New Zealand Chapter of the ACM Special Interest Group on Computer-Human Intera 2011
DOI: 10.1145/2000756.2000765
|View full text |Cite
|
Sign up to set email alerts
|

Learning outcome dependency on contemporary ICT in the New Zealand middle school classroom

Abstract: Often studies of children"s technology use in the classroom is internally focused and small scale. This study attempts a globalised exploratory overview of an entire New Zealand middle school to understand the technology usages across a range of curriculum and learning outcomes. Observations of the use of technology in the classroom during eight different lessons were conducted followed by structuredopen-ended interviews. From our classroom observations and through teacher interviews, we have been able to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…In earlier work we observed how children in the NZ classrooms and homes used a broad range of technologies including digital whiteboards, laptops, and tablets and a range of child‐targeted software for skill‐based learning (e.g. reading and maths) (Timpany & Vanderschantz, ; Vanderschantz, Hinze, & Cunningham, ). This is similar to the situation globally with studies confirming that, worldwide, child‐specific software is seeing significant use in primary education: for example, for reading and searching (i.e., Hutchinson et al, ), and novel teaching of mathematics and programming using tablets, software and haptic devices (i.e., Hegedus, ).…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work we observed how children in the NZ classrooms and homes used a broad range of technologies including digital whiteboards, laptops, and tablets and a range of child‐targeted software for skill‐based learning (e.g. reading and maths) (Timpany & Vanderschantz, ; Vanderschantz, Hinze, & Cunningham, ). This is similar to the situation globally with studies confirming that, worldwide, child‐specific software is seeing significant use in primary education: for example, for reading and searching (i.e., Hutchinson et al, ), and novel teaching of mathematics and programming using tablets, software and haptic devices (i.e., Hegedus, ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…based learning (e.g. reading and maths) (Timpany & Vanderschantz, 2011;Vanderschantz, Hinze, & Cunningham, 2014a). This is similar to the situation globally with studies confirming that, worldwide, child-specific software is seeing significant use in primary education: for example, for reading and searching (i.e., Hutchinson et al, 2007), and novel teaching of mathematics and programming using tablets, software and haptic devices (i.e., Hegedus, 2013).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Similarly there has been a focus on the use of software and devices for the creation of digital media such as video, photography, and digital storytelling (Tsai, Shen, & Lin, 2015). Our own research has previously observed that children in NZ classrooms use this full range of technologies during their education (Timpany & Vanderschantz, 2011;Vanderschantz et al, 2014a).…”
Section: Ict In Nz Educationmentioning
confidence: 98%
“…In NZ information seeking is formalised in education through the common pedagogical practices of inquiry-based learning. The breadth of information seeking tools and ICTs found in NZ classroom"s and schools includes a variety of digital books, eBooks, and Internet resources, OPAC systems, and specific educational software (Timpany & Vanderschantz, 2011).…”
Section: Ict In Nz Educationmentioning
confidence: 99%
“…More specifically, there is a lack of research around best practices for the design of this material for children. Timpany and Vanderschantz (2011) show that children in the classroom can be observed to use a range of technologies during their typical educational pursuits. Today these technologies include digital whiteboards, laptop computers and mobile tablet and personal touch screen interactive devices such as the iPod and iPad.…”
Section: Introductionmentioning
confidence: 99%